Feasability of An Eccentric Isokinetic Protocol to Induce Trunk Muscle Damage: A Pilot Study - Engel, Tilman; Schraplau, Anne; Wochatz, Monique; Kopinski, Stephan; Sonnenburg, Dominik; Schomoeller, Anne; Risch, Lucie; Kaplick, Hannes; Mayer, Frank (Sports Medicine International Open, 2022)
Eccentric exercise is discussed as a treatment option for clinical populations, but specific responses in terms of muscle damage and systemic inflammation after repeated loading of large muscle groups have not been conclusively characterized. Therefore, this study tested the feasibility of an isokinetic protocol for repeated maximum eccentric loading of the trunk muscles. Nine asymptomatic participants (5 f/4 m; 34±6 yrs; 175±13 cm; 76±17 kg) performed three isokinetic 2-minute all-out trunk strength tests (1x concentric (CON), 2x eccentric (ECC1, ECC2), 2 weeks apart; flexion/extension, 60°/s, ROM 55°). Outcomes were peak torque, torque decline, total work, and indicators of muscle damage and inflammation (over 168 h). Statistics were done using the Friedman test (Dunn’s post-test). For ECC1 and ECC2, peak torque and total work were increased and torque decline reduced compared to CON. Repeated ECC bouts yielded unaltered torque and work outcomes. Muscle damage markers were highest after ECC1 (soreness 48 h, creatine kinase 72 h; p<0.05). Their overall responses (area under the curve) were abolished post-ECC2 compared to post-ECC1 (p<0.05). Interleukin-6 was higher post-ECC1 than CON, and attenuated post-ECC2 (p>0.05). Interleukin-10 and tumor necrosis factor-α were not detectable. All markers showed high inter-individual variability. The protocol was feasible to induce muscle damage indicators after exercising a large muscle group, but the pilot results indicated only weak systemic inflammatory responses in asymptomatic adults.
Keywords: exercise; eccentric; muscle fatigue; trunk muscles; isokinetics; repeated bout effect; inflammation; exercise induced muscle damage; interleukin-6; internleukin-10; tumor necrosis factor-α